1999
DOI: 10.1046/j.1464-410x.1999.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐sitosterol for the treatment of benign prostatic hyperplasia:

Abstract: Objectives To conduct a systematic review of the eviInternational Prostate Symptom Score (IPSS), the weighted mean diCerence (WMD) against placebo was dence for the eBcacy of b-sitosterol in men with symptomatic benign prostatic hyperplasia (BPH).−4.9 IPSS points (95% confidence interval, CI,−6.3 to−3.5). The WMD for peak urinary flow rate was Methods Studies were identified through Medline@ (1966-98), EMBASE@, Phytodok, the Cochrane 3.91 mL/s (95% CI 0.91 to 6.90, four studies) and for residual volume the WM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(64 citation statements)
references
References 23 publications
4
53
0
7
Order By: Relevance
“…This type of research has shown a number of actions produced by BS: it was able to inhibit both vascular adhesion and intracellular adhesion molecule 1 expression in TNF-alpha-stimulated human aortic endothelial cells; in 2,4-dinitrofluorobenzene-induced mouse dermatitis, it was able to significantly reduce the clinical severity by inhibiting the infiltration of inflammatory cells, and the levels of IgE, interleukin-4, and histamine in the serum of treated mice; also, in the mouse carrageenan-induced inflammation air pouch model, it was determined that the chemical promoted a time-and dose-dependent increase of the calcium uptake in activated neutrophils, and inhibited myeloperoxidase, adenosine deaminase, interleukin-1 and the tumor necrosis factor. The mentioned effects, as well as the findings of the present report, support the suggested beneficial effects of BS for a number of diseases, which include benign prostatic hyperplasia, colon and breast cancer, atherosclerosis, and gastrointestinal ulceration (Wilt et al, 1999;Choudary and Trans, 2011;Hewing and Fisher, 2012;Tovey, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…This type of research has shown a number of actions produced by BS: it was able to inhibit both vascular adhesion and intracellular adhesion molecule 1 expression in TNF-alpha-stimulated human aortic endothelial cells; in 2,4-dinitrofluorobenzene-induced mouse dermatitis, it was able to significantly reduce the clinical severity by inhibiting the infiltration of inflammatory cells, and the levels of IgE, interleukin-4, and histamine in the serum of treated mice; also, in the mouse carrageenan-induced inflammation air pouch model, it was determined that the chemical promoted a time-and dose-dependent increase of the calcium uptake in activated neutrophils, and inhibited myeloperoxidase, adenosine deaminase, interleukin-1 and the tumor necrosis factor. The mentioned effects, as well as the findings of the present report, support the suggested beneficial effects of BS for a number of diseases, which include benign prostatic hyperplasia, colon and breast cancer, atherosclerosis, and gastrointestinal ulceration (Wilt et al, 1999;Choudary and Trans, 2011;Hewing and Fisher, 2012;Tovey, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Linoleic acid has possessed many biological activities such as anti-inflammatory, hypocholesterolemic cancer preventive, nematicide insectifuge, hepatoprotective, antihistamines, antiacne, antiarthritis, antieczemic, 5-alpha-reductase inhibitor, antiandrogenic, and anticoronary [16]. While the β-sitosterol also found the main compound in this plant has been reported the ability in the reduction of the growth and the multiplication on prostate cancer cell lines [17][18][19]. From the GC-MS analysis results, these major compounds could be responsible for the medicinal properties which support C. sappan for the treatment of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…58 Trials lasted 4-26 weeks. It found that sitosterol significantly reduced the international prostate symptom score (2 RCTs, WMD − 4.9 points, − 6.3 to − 3.5).…”
Section: Benefitsmentioning
confidence: 99%
“…Withdrawal rates were similar in both groups (7.8% in men taking sitosterol v 8.0% taking placebo, significance not stated). 58 …”
Section: Harmsmentioning
confidence: 99%